Priority setting in responding crisis: a hospital leaders’ perspective at the early stage of COVID-19 pandemic - Aryo Dewanto; Yudi Setyawan; Viera Wardhani (Health Science Journal of Indonesia, 2021)
Background: The COVID-19 pandemic hit Indonesia when hospitals were striving to adjust to a changing environment after a new health insurance system implementation, a government’s effort to achieve Universal Health Coverage. As a result, the pandemic forced hospitals to exploit their resources. Due to limited resources, setting accurate priorities is highly important to secure hospital operations and maintain its track towards the expected goals. This study aims to explore how deep the crisis impacts hospitals and how hospital leaders in Indonesia set their priorities in responding to the impact of this pandemic. Methods: This study used a descriptive and analytical approach. Data were collected through an online survey from hospital leaders and several documentary sources. Results: The results show that almost all hospital directors consider patient visits and hospital finance the most significant impacts of the COVID-19 pandemic. However, government hospital directors emphasize different areas compared to non-government hospital directors; the former sets their priorities on the hospital’s human resources, quality of service, and operations, while the latter focuses on the impact of patient visits and hospital finance. Conclusion: Although directors of government and non-governmental hospitals have a different emphasis, their priority is the same, maintaining hospital sustainability to provide quality services to people. Keywords: COVID-19 pandemic, hospital leaders’ perspective, impacts, Indonesia, priority setting Abstrak Latar belakang: Pandemi COVID-19 melanda Indonesia ketika rumah sakit berusaha menyesuaikan diri dengan lingkungan yang berubah setelah penerapan sistem jaminan kesehatan baru sebagai upaya pemerintah untuk mencapai Universal Health Coverage. Akibatnya, pandemi memaksa rumah sakit untuk mengeksploitasi sumber daya mereka. Sumber daya yang terbatas membuat penetapan prioritas yang akurat menjadi sangat penting untuk menjamin keberlangsungan operasional rumah sakit dan memastikan rumah sakit bergerak menuju tujuan yang diharapkan. Penelitian ini bertujuan untuk mengeksplorasi seberapa dalam dampak krisis ini terhadap rumah sakit dan bagaimana pemimpin rumah sakit di Indonesia menetapkan prioritasnya dalam merespon dampak pandemi ini. Metode: Penelitian ini menggunakan pendekatan deskriptif dan analitik. Data dikumpulkan melalui survei online dari pimpinan rumah sakit dan beberapa sumber dokumenter. Hasil: Hasil penelitian menunjukkan bahwa hampir semua direktur rumah sakit menganggap kunjungan pasien dan pembiayaan rumah sakit mendapat dampak paling signifikan dari pandemi COVID-19. Namun, direktur rumah sakit pemerintah menekankan bidang yang berbeda dibandingkan dengan direktur rumah sakit non-pemerintah. Direktur rumah sakit pemerintah menetapkan prioritas mereka pada sumber daya manusia rumah sakit, kualitas layanan, dan operasi, sedangkan direktur rumah sakit non-pemerintah fokus pada dampak kunjungan pasien dan keuangan rumah sakit. Kesimpulan: Meskipun direktur rumah sakit pemerintah dan non-pemerintah memiliki penekanan yang berbeda, tetapi prioritas mereka sama yaitu menjaga keberlanjutan rumah sakit untuk memberikan pelayanan yang berkualitas kepada masyarakat. Kata kunci: pandemi COVID-19, perspektif pemimpin rumah sakit, dampak, Indonesia, penetapan prioritas.